Xyloketal B Attenuates Atherosclerotic Plaque Formation and Endothelial Dysfunction in Apolipoprotein E Deficient Mice - Li-Yan Zhao (Marine Drugs, 2015)
Our previous studies demonstrated that xyloketal B, a novel marine compound with a unique chemical structure, has strong antioxidant actions and can protect against endothelial injury in different cell types cultured in vitro and model organisms in vivo. The oxidative endothelial dysfunction and decrease in nitric oxide (NO) bioavailability are critical for the development of atherosclerotic lesion. We thus examined whether xyloketal B had an influence on the atherosclerotic plaque area in apolipoprotein E-deficient (apoE−/−) mice fed a high-fat diet and investigated the underlying mechanisms. We found in our present study that the administration of xyloketal B dose-dependently decreased the atherosclerotic plaque area both in the aortic sinus and throughout the aorta in apoE−/− mice fed a high-fat diet. In addition, xyloketal B markedly reduced the levels of vascular oxidative stress, as well as improving the impaired endothelium integrity and NO-dependent aortic vasorelaxation in atherosclerotic mice. Moreover, xyloketal B significantly changed the phosphorylation levels of endothelial nitric oxide synthase (eNOS) and Akt without altering the expression of total eNOS and Akt in cultured human umbilical vein endothelial cells (HUVECs). Here, it increased eNOS phosphorylation at the positive regulatory site of Ser-1177, while inhibiting phosphorylation at the negative regulatory site of Thr-495. Taken together, these findings indicate that xyloketal B has dramatic anti-atherosclerotic effects in vivo, which is partly due to its antioxidant features and/or improvement of endothelial function.